OPTIMASI KINERJA PELABUHAN RORO AIR PUTIH BENGKALIS - Riswanda, Aidil; Saputra, Hendra; Lisya, Mutia (Jurnal TeKLA, 2024)
Air Putih RoRo Port is a port with very dense crossing activities, with vehicle queue conditions that exceed ship services on weekdays and national holidays, so it is necessary to evaluate port performance to get steady state, optimal ship service time and port productivity growth. The methods used in evaluating port performance due to vehicle queues and ship services are using the steady state substitution method and least squares linear regression. The results of the analysis with the steady state substitution method by adding 1 pier, the steady state value becomes < 1 and using the least squares linear regression method, the annual growth value of passengers is 5.32%, two-wheeled vehicles 4.61%, four-wheeled vehicles 9.15%, and six-wheeled vehicles 8.41%. From this analysis, it can be concluded that the addition of 1 pier the level of ship service is optimal in handling vehicle queues and passenger / vehicle productivity increases every year at the Air Putih RoRo Port.